THE POSSIBILITIES OF THE INFLUENCE OF BRONCHIAL ASTHMA AND COPD ON OUTCOMES AND SURVIVAL RATES IN PATIENTS WITH COVID-19 (World Bulletin of Public Health, 2024)
It is known that the presence of certain concomitant diseases can provoke a severe course of COVID19 and increase mortality among patients. However, the question of the possible impact of bronchial asthma and COPD on outcomes and survival rates in patients with COVID-19 remains relevant.
Keywords: Bronchial asthma; COVID-19; SARS-CoV-2 coronavirus infection